Learning to cycle: a constraint-led intervention programme using different cycling task constraints - Mercê, Cristiana (2023)
Background: Cycling is a foundational movement skill which represents an important motor milestone to achieve in children’s lives. The use of a bicycle with training wheels is the most common approach for learning how to cycle, although some evidence suggests that this approach is counterproductive. Purpose: Underpinned by an ecological perspective and Constraints-led approach, this study investigated whether learning how to ride a conventional bicycle in childhood can be shaped by the specific task constraints related to the kind of training bicycle used beforehand (i.e. balance bike or bicycle with training wheels). This comparison could guide pedagogical practice to facilitate children’s learning in cycling and their independent riding. Methods: The Learning to Cycle intervention programme was introduced to 25 children (M = 6.08 ± 1.19 years) who could not previously cycle, divided into two treatment groups. One group trained with a bicycle with training wheels (BTW) and another with a balance bicycle (BB) for six sessions, followed by four sessions with a conventional bicycle (CB). The acquisition of independent cycling was assessed, based on established cycle learning milestone achievements, without help: (i) selflaunch, (ii) riding for at least 10 (consecutive) metres, and (iii), braking. To be considered an independent rider, participants needed to achieve all these milestones, without any external help. During the CB sessions, the number of sessions that each child needed to acquire each learning milestone and independent cycling were recorded. Results: The programme led to a success rate of 88% for achievement of independent cycling on a conventional bicycle, differentiated by 100% success in the BB group and 75% in the BTW group. The BB participants were significantly faster in learning to self-launch, ride, brake, and cycle independently, compared to BTW participants. Conclusions: The Learning to Cycle programme was effective for facilitating learning in children from three years of age onwards. Using the BB instead of the BTW seems to lead to a more effective and efficient acquisition of independent cycling at earlier ages.